Pengaruh Kepemimpinan Tranformasional terhadap Kinerja Pegawai pada Kantor Distrik Sorong Kota - Jecklyn Waromi; Andrei Maryen; Rendy Patiasina (Journal on Education, 2023)
This study aims to analyze the influence of transformational leadership on employee performance at the Sorong City District Office. The data analysis method used is quantitative analysis. significant test through (t-test), using simple linear regression and the coefficient of determination (R2). The population in this study were all employees at the Sorong City District Office. a sample of 30 respondents. Primary data obtained through interviews, questionnaires and documentation studies. From the results of data processing simple linear regression analysis using the SPSS for windows version 25 program, the regression equation Y = 8.466 + 0.679X, the regression coefficient value of 0.679 means that every time there is a change and one percent addition to the Transformational Leadership variable, the Employee Performance variable will increase is 0.679, if the Transformational Leadership variable is zero, then Employee Performance has a value of 8.466. In the test the coefficient of determination obtained R square 64.9%, meaning that Transformational Leadership influences Employee Performance by 64.9%, while the remaining 35.1% is influenced by other factors not analyzed in this study, namely work culture. The results of the t test, where tcount 7.1935 > ttable 1.7011, it can be said that the Variable Transformational Leadership has a positive and significant effect on Employee Performance.